2016
DOI: 10.1590/0103-8478cr20151051
|View full text |Cite
|
Sign up to set email alerts
|

Firocoxib on aqueous humor prostaglandin E 2 levels for controlling experimentally-induced breakdown of blood-aqueous barrier in healthy and Toxoplasma gondii -seropositive cats

Abstract: Efeitos do firocoxib sobre os níveis de prostaglandina E 2 no humor aquoso de gatos saudáveis e com sorologia positiva para toxoplasmose mediante quebra da barreira hematoaquosa experimentalmente induzida

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…28 It has been reported that the intravenous administration of epinephrine increases the HR and MAP significantly in cats anesthetized with isoflurane, 17 whereas lidocaine appears to be associated with cardiovascular depression. 19 Considering that blood-aqueous barrier is disrupted following anterior chamber paracentesis in cats, 29,30 one should assume that both epinephrine and lidocaine might be absorbed systemically inducing to changes in cardiovascular parameters. In our study, cats that received epinephrine developed significantly higher MAP, in the first 20 minutes of evaluation, than the ones treated with both doses of lidocaine.…”
Section: Epinephrinementioning
confidence: 99%
“…28 It has been reported that the intravenous administration of epinephrine increases the HR and MAP significantly in cats anesthetized with isoflurane, 17 whereas lidocaine appears to be associated with cardiovascular depression. 19 Considering that blood-aqueous barrier is disrupted following anterior chamber paracentesis in cats, 29,30 one should assume that both epinephrine and lidocaine might be absorbed systemically inducing to changes in cardiovascular parameters. In our study, cats that received epinephrine developed significantly higher MAP, in the first 20 minutes of evaluation, than the ones treated with both doses of lidocaine.…”
Section: Epinephrinementioning
confidence: 99%